PENGARUH HEURISTIC DAN ISSUE VOTING TERHADAP PEROLEHAN SUARA PRABOWO SUBIANTO - SANDIAGA SALAHUDDIN UNO PADA PEMILIHAN PRESIDEN DAN WAKIL PRESIDEN TAHUN 2019 DI KOTA BOGOR : Array - Friantika Resti Karina; Dede Sri Kartini; Hendra (Program Studi Ilmu Pemerintahan FISIP Universitas Galuh, 2021)
During the 2019 Presidential Election, the public could hardly avoid political exposure in the form of information & issues that even rolled around long before this election stage took place. This information / issue is used as material for voters to consider their choice. This is called issue voting, which consists of hard issues and easy issues. In addition, with the large amount of information / issues circulating, not a few people handle the excess information they have through heuristic means, one of which is by allowing other people outside of themselves to make decisions, which is called endorsement. Based on the results of the survey and the opinions of several observers, there are various reasons for Prabowo-Sandi winning in Bogor City. In this context, the main factors are issue and endorsement. This is the reason the author conducted a research entitled